POLITICAL COMMUNICATION OF DEMOCRATIC POLITICAL LEADERS, DR. ATHIT URAIRAT - Khongaiad, Phatsorn; Torkaew, Vittayatorn; Boonsiri, Karn (Journal of Social Science and Cultural, 2024)
The purpose of this research is to1) Study the political path that affects political communication of democratic political leaders, Dr. Athit Ourairat, during the period between 1988-2006 2) Study the political communication process of democratic political leaders, Dr. Athit Ourairat, during the period between 1988-2006 3) Study the political communication methods of democratic political leaders, Dr. Athit Ourairat, during the period between 1988-2006 and 4) study the political communication strategies of democratic political leader Dr. Athit Urairat during the period between 1988-2006 and 4) study the political communication strategies of democratic political leader Dr. 1988-2006 This research is qualitative research with in - depth interviews with specific key informants. There were a total of 18 informants divided into 7 groups. The research instrument was a structured in - depth interview to analyze the data by drawing conclusions. The results of the research found that 1) The political path of Dr. Athit Ourairat during the period 1988-2006, Dr. Athit Ourairat until his retirement from politics. He has solved many of the country's problems and crises. 2) Dr. Athit Urairat's political communication process is a good political messenger and communicates politics in the style of Dhammathirat, which makes him successful in communication. Political 3) Dr. Athit Ourairat's method of political communication is giving lectures using the principles of rhetoric. and using the principles of logic in citing reasons to persuade people, and 4) Dr. Athit Urairat's political communication strategies have good persuasion strategies and rhetoric in political communication.